Molecular characterization of Quercus suber MYB1, a transcription factor up-regulated in cork tissues - Almeida, Tânia; Menéndez, Esther; Capote, Tiago; Ribeiro, Teresa; Santos, Conceição; Gonçalves, Sónia (Journal of Plant Physiology, 2012)
The molecular processes associated with cork development in Quercus suber L. are poorly understood. A previous molecular approach identiﬁed a list of genes potentially important for cork formation and differentiation, providing a new basis for further molecular studies. This report is the ﬁrst molecular characterization of one of these candidate genes, QsMYB1, coding for an R2R3-MYB transcription factor. The R2R3-MYB gene sub-family has been described as being involved in the phenylpropanoid and lignin pathways, both involved in cork biosynthesis. The results showed that the expression of QsMYB1 is putatively mediated by an alternative splicing (AS) mechanism that originates two different transcripts (QsMYB1.1 and QsMYB1.2), differing only in the 5 -untranslated region, due to retention of the ﬁrst intron in one of the variants. Moreover, within the retained intron, a simple sequence repeat (SSR) was identiﬁed. The upstream regulatory region of QsMYB1 was extended by a genome walking approach, which allowed the identiﬁcation of the putative gene promoter region. The relative expression pattern of QsMYB1 transcripts determined by reverse transcription quantitative polymerase chain reaction (RTqPCR) revealed that both transcripts were up-regulated in cork tissues; the detected expression was several times higher in newly formed cork harvested from trees producing virgin, second or reproduction cork when compared with wood. Moreover, the expression analysis of QsMYB1 in several Q. suber organs showed very low expression in young branches and roots, whereas in leaves, immature acorns or male ﬂowers, no expression was detected. These preliminary results suggest that QsMYB1 may be related to secondary growth and, in particular, with the cork biosynthesis process with a possible alternative splicing mechanism associated with its regulatory function.
The following values have no corresponding Zotero field: accession-num: 23218545
Keywords: Alternative Splicing; Amino Acid Sequence; Cork biosynthesis; Cork oak; Gene Expression Regulation; Genes; Lipids; Lipids: biosynthesis; Molecular Sequence Data; phellogen; Plant; Plant Bark; Plant Bark: genetics; Plant Bark: metabolism; Plant Growth Regulators; Plant Growth Regulators: biosynthesis; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; RNA; Transcription Factors; Transcription Factors: chemistry; Transcription Factors: metabolism; Up-Regulation

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
The following values have no corresponding Zotero field: accession-num: 17503092
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation